COVID19: potential cardiovascular issues in pediatric patients - Bertoncelli, Deborah; Guidarini, Marta; Della Greca, Anna; Ratti, Chiara; Falcinella, Francesca; Dutto, Mauro Luigi; Tchana, Bertrand (Acta Biomedica Atenei Parmensis, 2020)
The novel severe acute respiratory syndrome coronavirus 2 (SARS-COV 2) has rapidly spread worldwide with increasing hospitalization and mortality rate. Ongoing studies and accumulated data are de- tailing the features and the effects of the new coronavirus disease 19 (COVID 19) in the adult population, and cardiovascular involvement is emerging as the most significant and life-threatening complication, with an in- creased risk of morbidity and mortality in patients with underlying cardiovascular disease. At present, though the limited data on the effects of COVID 19 in pediatric patients, children seem to count for a little proportion of SARS-COV 2 infection, and present with less severe disease and effects However infants and toddlers are at risk of developing critical course. The disease has a range of clinical presentations in children, for which the potential need for further investigation of myocardial injury and cardiovascular issues should be kept in mind to avoid misdiagnosing severe clinical entities. Overlapping with Kawasaki disease is a concern, particularly the incomplete and atypical form. We aim to summarize the initial considerations and potential cardiovascular implications of COVID-19 for children and patients with congenital heart disease.